Pulmonary cryptococcosis presenting as acute severe respiratory distress in a newly diagnosed HIV patient in Tanzania: a case report. Issue 9 (11th August 2015) - Gunda, Daniel W.; Bakshi, Fatma A.; Rambau, Peter; Kilonzo, Semvua B.
Key Clinical Message: Pulmonary cryptococcosis is a common condition in HIV‐infected patients which is frequently missed or misdiagnosed in resource‐limited countries. We report a case of HIV/AIDS patient who was misdiagnosed with a fatal outcome. There is a need to implement screening tools to be used where the diagnosis may not be confirmed. Abstract : Pulmonary cryptococcosis is a common condition in HIV‐infected patients which is frequently missed or misdiagnosed in resource‐limited countries. We report a case of HIV/AIDS patient who was misdiagnosed with a fatal outcome. There is a need to implement screening tools to be used where the diagnosis may not be confirmed.